Contextualizing Groundwater crisis in the light of Disaster Risk Management in India - Ashutosh Raj Anand; Mary Peters (Fakultas Hukum Universitas Lampung, 2022)
Water is indispensable for human life. As a matter of fact, any economy is inextricably linked with availability of this essential resource. Traditionally water has not been a scarce resource in India. In the wake of massive demand stemming from various sectors has led to the fast shrinkage and disappearance of water bodies from the landscape. The situation is especially grave when it comes to groundwater as this resource is acutely threatened in many parts of the country due to overexploitation. The present paper is an attempt to explicate the current legal framework which governs groundwater. Especially in the context of disaster risk triggered by varied hazards the issue pertaining to groundwater should also be seen as human induced disaster. Climate changes contribute to extreme events such as drought which adversely affect groundwater resource. Therefore, attempt is also made in this paper to unravel the extant legal framework on disaster. Paper assesses India’s institutional framework which are responsible to disaster risk management and analyze how it has a bearing on securing ground water resources.